2018
DOI: 10.3102/0013189x18787818
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional and Longitudinal Disparities in STEM Career Aspirations at the Intersection of Gender, Race/Ethnicity, and Socioeconomic Status

Abstract: Analyzing the nationally representative High School Longitudinal Study of 2009 (HSLS:09), this study examined the cross-sectional and longitudinal disparities in STEM career aspirations at the intersection of gender, race/ethnicity, and socioeconomic status (SES). Results indicated that female, Black, Hispanic, and low SES students were less likely to show, maintain, and develop an interest in STEM careers during high school years. Compared with White boys from higher SES background, girls from all racial/ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 11 publications
3
71
0
6
Order By: Relevance
“…Whereas existing research tends to suggest that a higher SES is linked to a higher participation rate of structured OST programs given the cost (Mahoney, Larson, et al, 2005;Vandell et al, 2005), this general trend was not found among Latinx adolescents, who tend to have the lowest participation rate in OST programs (Darling, 2005;Meier et al, 2018). This finding signals to researchers and practitioners that racial/ethnic identity or SES alone may not constitute a salient factor to predict Latinx students' OST program participation (Saw et al, 2018).…”
Section: Sociodemographic Differences and Intersectionality Manifesmentioning
confidence: 71%
See 2 more Smart Citations
“…Whereas existing research tends to suggest that a higher SES is linked to a higher participation rate of structured OST programs given the cost (Mahoney, Larson, et al, 2005;Vandell et al, 2005), this general trend was not found among Latinx adolescents, who tend to have the lowest participation rate in OST programs (Darling, 2005;Meier et al, 2018). This finding signals to researchers and practitioners that racial/ethnic identity or SES alone may not constitute a salient factor to predict Latinx students' OST program participation (Saw et al, 2018).…”
Section: Sociodemographic Differences and Intersectionality Manifesmentioning
confidence: 71%
“…Prior research has found that high school students' interest in STEM fields vary by the intersections between their gender, race/ethnicity, and SES (Saw, Chang, & Chan, 2018). Even after entering college and starting to take STEM-focused courses, the relationship between students' self-efficacy in STEM and academic achievement varies by the intersection of their sociodemographic backgrounds (Wang, Chan, Soffa, & Nachman, 2017).…”
Section: Sociodemographic Differences In Stem Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…High SES is associated with higher achievement in language function tasks (Calvo and Bialystok 2014). Finally, Saw et al (2018) show that low SES students are less likely to cultivate and retain an interest in science, technology, engineering, and math careers.…”
Section: Introductionmentioning
confidence: 90%
“…We examine these beliefs based on variables of gender, ethnicity, general test taking anxiety, and past experiences with high-stakes testing. We know that educational experiences vary widely by gender and ethnicity (Alemán, 2018;Bailey & Graves, 2016;Sadker, Sadker, & Klein 1991;Saw, Chang, & Chan, 2018;Valenzuela, 1999), especially as it relates to highstakes testing (Nichols & Berliner, 2007;Vasquez Heilig & Darling-Hammond, 2008). Thus, we include gender and ethnicity in our analyses along with prior experiences with high-stakes testing to explore how those lived experiences may relate to beliefs about accountability and high-stakes testing as well as preferences for future working conditions.…”
Section: Theoretical Rationalesmentioning
confidence: 99%